Search for a standard model Higgs boson in the mass range 200-600 GeV in the H→ZZ→l+l−qq [bar] decay channel with the ATLAS detector* - Aad, Georges; Anders, Gabriel; Anders, Christoph; Andrei, George Victor; Davygora, Yuriy; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Kasieczka, Gregor; Khomich, Andrei; Kluge, Eike-Erik; et al. (Physics letters, 2012)
A search for a heavy Standard Model Higgs boson decaying via H→ZZ→ℓ+ℓ−qq¯, where ℓ=e or μ, is presented. The search uses a data set of pp collisions at s=7 TeV, corresponding to an integrated luminosity of 4.7 fb−1 collected in 2011 by the ATLAS detector at the CERN LHC. No significant excess of events above the estimated background is found. Upper limits at 95% confidence level on the production cross section of a Higgs boson with a mass in the range between 200 and 600 GeV are derived. A Standard Model Higgs boson with a mass in the range 300 GeV⩽mH⩽322 GeV or 353 GeV⩽mH⩽410 GeV is excluded at 95% CL. The corresponding expected exclusion range is 351 GeV⩽mH⩽404 GeV at 95% CL.